Self‐Assembled Anion‐Binding Cryptand for the Selective Liquid–Liquid Extraction of Phosphate Anions - Andrews, Rebecca; Begum, Sabera; Clemett, Christopher J.; Faulkner, Robert A.; Ginger, Michael L.; Harmer, Jane; Molinari, Marco; Parkes, Gareth M. B.; Qureshi, Zuhlqurnain M. H.; Rice, Craig R.; Ward, Michael D.; Williams, Howard M.; et al. (Angewandte Chemie International Edition, 2020)
The ligands L1 and L2 form trinuclear self‐assembled complexes with Cu2+ (i.e. [(L1)2Cu3]6+ or [(L2)2Cu3]6+) both of which act as a host to a variety of anions. Inclusion of long aliphatic chains on these ligands allows the assemblies to extract anions from aqueous media into organic solvents. Phosphate can be removed from water efficiently and highly selectively, even in the presence of other anions. The ligands L1 and L2 form trinuclear self‐assemblies with Cu2+ (i.e. [L2Cu3]6+) both of which act as hosts to a variety of anions. Inclusion of long aliphatic chains on these ligands allows the self‐assemblies to extract anions from aqueous media into organic solvents. Phosphate anions can be removed from water efficiently and highly selectively in the presence of other anions.